An adsorption resin having a low electron cloud density amidoxime group, and a preparation method and application thereof
Patent Information
- Application Number
- CN202611188438.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-30
AI Technical Summary
解决现有偕胺肟吸附树脂镓吸附速率低,吸附容量小和镓吸附选择性差的问题
[0017]本发明具有以下有益效果:本发明通过在树脂上加入吸电子基团来调节偕胺肟基团的电子云密度,吸电子基团的存在有助于偕胺肟基团去质子化,降低了树脂的pKa,增加树脂整体的活性点位,从而提高树脂的饱和吸附容量,加快初始吸附速率,从而提高对镓吸附的特异选择性。试验结果表明,本发明的具有低电子云密度偕胺肟基团的吸附树脂相比于对比例的吸附树脂,其pKa更低,去质子化程度更高,镓吸附活性位点更丰富,在吸附初期实现对镓的快速吸附从而具有吸附选择性。
Smart Images

Figure CN123003783A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional polymer compound technology, specifically to an adsorption resin with low electron cloud density amine oxime groups, its preparation method, and its application. Background Technology
[0002] Gallium is an important strategic metal with significant applications in high-tech fields such as computers, communications, aerospace, new energy, medicine and healthcare, and military industry. Gallium is a rare and dispersed metal, lacking independent deposits in nature and often occurring within the crystal lattices of other minerals. It is typically recycled as a byproduct of other metal production. Bauxite is the most important gallium-containing resource; currently, approximately 90% of gallium is extracted from Bayer mother liquor during the alumina production process. The main methods for gallium extraction include chemical precipitation, amalgamation, solvent extraction, and resin adsorption. Compared to the other three methods, resin adsorption offers significant advantages for gallium extraction from Bayer mother liquor, featuring a shorter process flow, faster reaction kinetics, higher recovery rates, and lower requirements for gallium ion concentration in the solution. The key to gallium extraction from Bayer mother liquor is the use of high-quality, low-cost adsorption resins. These resins must be stable in strongly alkaline sodium aluminate solutions, selectively extracting gallium from them, and exhibiting good recyclability to meet industrial requirements. Currently, due to their selective adsorption of gallium (Bayer's mother liquor contains a lot of Al, but the amylopectin structure hardly adsorbs Al) and their chemical stability and durability in strongly alkaline environments, amylopectin-based adsorption resins are the most important adsorption resins for extracting gallium from Bayer's mother liquor in industrial production. However, existing amylopectin adsorption resins have very high pKa values (i.e., low degree of ionization, making ionization (oxime deprotonation) difficult). Even in the strongly alkaline environment of Bayer's mother liquor, the degree of oxime deprotonation is very low (degree of ionization less than 50%), making it difficult to generate enough active adsorption sites, resulting in small gallium adsorption capacity and low adsorption rate.
[0003] To address the aforementioned issues, existing work on gallium modification of amine oxime adsorption resins primarily focuses on adjusting the resin's physical morphology and pore structure, and introducing additional functional groups for synergistic adsorption. For example, a novel composite adsorbent, PAO / SiO2, was prepared by using silica (SiO2) as the core, grafting polyacrylonitrile (PAN) via solution polymerization, and then functionalizing it with amine oximes. Compared to the traditional commercial resin (LSC-600), this material exhibits a smaller particle size (170–180 μm) and a larger specific surface area (133.4 m²). 2The presence of more abundant pore structures (e.g., g) is beneficial for improving mass transfer efficiency. A MOF surface functionalization strategy using amine oximes can increase the specific surface area of the amine oxime adsorption resin and improve the gallium adsorption rate. Crosslinked polyethylene amine oxime fibers (HPAO) were prepared in a two-step process using PAN fibers as raw materials and hydrazine hydrate as a crosslinking agent. Adjusting the crosslinking time altered the fiber density, improving the resin's hydrophilicity and stability. PAN / PVA composite fibers were prepared using a simple blending and electrospinning process with PAN and PVA. Then, PAN was amine-oximeized to obtain PAN-AO / PVA adsorbents. PVA broke the original intramolecular hydrogen bonds of PAN-AO, reconstructing them into intermolecular hydrogen bonds between PAN-AO and PVA, thus improving fiber porosity, hydrophilicity, and the number of amine oxime groups. However, the above methods cannot address the problem of high pKa in amine oxime adsorption resins, and even in strongly alkaline Bayer mother liquor environments, the low degree of oxime deprotonation leading to a limited number of effective active adsorption sites. Summary of the Invention
[0004] To address the aforementioned shortcomings of existing technologies, the present invention aims to provide an adsorption resin with low electron cloud density amine oxime groups, its preparation method, and its applications. This is achieved by introducing electron-withdrawing groups at the ortho position of the amine oxime groups during resin synthesis, thereby reducing the electron cloud density of the amine oxime groups. The low electron cloud density of the amine oxime groups significantly reduces the pKa, greatly increases the degree of ionization, and increases the deprotonation rate, thus generating more active adsorption sites with high affinity for gallium (=NO). - This addresses the problems of low gallium adsorption rate, small adsorption capacity, and poor gallium adsorption selectivity in existing amine oxime adsorption resins.
[0005] The technical solution of the present invention to solve the above-mentioned technical problems is as follows: An adsorption resin with low electron cloud density amine oxime groups is provided, and the general structural formula of the adsorption resin is shown in formula (I):
[0006] (I) Wherein, R is at least one of -NO2, -CN, -CF3, -CCl3, -SO3H and halogen.
[0007] Furthermore, the halogen is at least one of F, Cl, Br and I.
[0008] This invention provides a method for preparing the above-mentioned adsorption resin with low electron cloud density amine oxime groups, comprising the following steps: (1) Preparation of porous copolymer microspheres: A1. Oil phase preparation: Mix the functional monomer, styrene containing electron-withdrawing groups, crosslinking agent and porogen, then add the initiator and mix well to obtain the oil phase system. A2. Aqueous phase preparation: Mix the aqueous dispersant and density regulator evenly, then add the dispersion stabilizer, and stir at 20-30℃ for 20-30 minutes to obtain the aqueous phase system; A3. Suspension and dispersion: Under stirring conditions and at 20℃-30℃, the oil phase system of A1 is added dropwise to the aqueous phase system of A2, and then the mixture is stirred at a constant temperature of 200-250r / min for 15-30min to obtain a suspension. A4. Heating polymerization: Under stirring conditions, the suspension of A3 is reacted at 60-70℃ for 1-3 hours; then the temperature is raised to 70-80℃ and the reaction is kept at a constant temperature for 2-4 hours; then the temperature is raised to 85-98℃ and the reaction is kept at a constant temperature for 3-5 hours. The resulting product is cooled to room temperature, filtered, and the resin beads are collected. A5. Post-treatment: The resin beads of A4 are washed sequentially with distilled water and 95%-99.9% ethanol, and then the resin beads are dried to obtain porous copolymer microspheres.
[0009] (2) The porous copolymer microspheres prepared in step (1) were modified by amine oxime modification: B1. Preparation of the oxime system: Dichloroethane, methanol, ethanol, water, triethylenetetramine solution, modifier and pH adjuster are mixed to prepare the oxime system; B2, Amine oxime reaction: The porous copolymer microspheres obtained in step (1) are added to the oxime system of B1 and reacted at 70-80℃ for 6-10 hours under stirring conditions. The resulting product is then filtered and the resin beads are collected to obtain the oxime resin. B3. Post-treatment of the amine oximated resin: The amine oximated resin of B2 is first washed with distilled water until the pH of the filtrate is 6.8-7.2, then washed with 95%-99.9% ethanol, and then dried to obtain the final product.
[0010] Furthermore, the functional monomer is acrylonitrile; the crosslinking agent is divinylbenzene; the porogen is at least one of cyclohexanone, isooctane, n-heptane, liquid paraffin, toluene, and xylene; and the initiator is benzoyl peroxide or azobisisobutyronitrile.
[0011] Furthermore, styrene containing electron-withdrawing groups is one of the following compounds:
[0012] Wherein, R is at least one of -NO2, -CN, -CF3, -CCl3, -SO3H and halogen.
[0013] Furthermore, the aqueous dispersant is deoxygenated distilled water; the density regulator is an aqueous NaCl solution; and the dispersant stabilizer is at least one of PVA1788, gelatin, carboxymethyl cellulose, and sodium lignosulfonate.
[0014] Furthermore, the modifier is hydroxylamine hydrochloride; the pH adjuster is NaOH.
[0015] This invention provides an application of the above-mentioned adsorption resin with low electron cloud density amine oxime groups in the extraction of gallium from bauxite.
[0016] The present invention also provides a method for extracting gallium from bauxite, which uses the above-mentioned adsorption resin with low electron cloud density amine oxime groups to extract gallium from bauxite by resin adsorption.
[0017] The present invention has the following beneficial effects: By adding electron-withdrawing groups to the resin, the electron cloud density of the amine oxime groups is adjusted. The presence of electron-withdrawing groups facilitates the deprotonation of the amine oxime groups, lowers the pKa of the resin, increases the overall active sites of the resin, thereby improving the saturated adsorption capacity of the resin, accelerating the initial adsorption rate, and thus improving the specific selectivity for gallium adsorption. Experimental results show that, compared with the comparative adsorption resin, the adsorption resin of the present invention with low electron cloud density amine oxime groups has a lower pKa, a higher degree of deprotonation, and more gallium adsorption active sites, achieving rapid adsorption of gallium in the initial adsorption stage, thus exhibiting adsorption selectivity. Attached Figure Description
[0018] Figure 1 XPS spectra of the adsorption resins in Examples 1, 7, and 8; Figure 2 The fine C1s spectra of the adsorption resins in Examples 1, 7, and 8 are shown below. Figure 3 The fine N1s spectra of the adsorption resins in Examples 1, 7, and 8 are shown below. Figure 4 The fine O1s spectra of the adsorption resins in Examples 1, 7, and 8 are shown below. Figure 5 The graph shows the relationship between the adsorption amount of gallium and vanadium and the adsorption time. Figure 6 The images show actual photos of the adsorption resins used in Examples 1, 7, and 8. Detailed Implementation
[0019] The examples given below are for illustrative purposes only and are not intended to limit the scope of the invention. Unless otherwise specified, conditions in the examples are performed under standard conditions or as recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0020] During the adsorption of gallium from Bayer mother liquor by the oxime adsorption resin, the main challenge is competition with vanadium (V) in the mother liquor for adsorption. In the mother liquor, gallium exists as the hydrated ion Ga(OH)4. -·nH2O, vanadium exists as hydrated ions VO4. 3- ·mH2O, due to the hydration radius (Ga(OH)4) - • nH2O is approximately 360 pm, VO4 3- ·mH2O is approximately 380 pm) and the charge it carries (Ga(OH)4) - H2O has a valence of -1, VO4 3- Due to the difference in oxidation state (H₂O is -3), gallium diffuses faster, while vanadium has a stronger affinity. During resin adsorption, gallium adsorption is typically fast initially and then slows down, while vanadium adsorption is slow initially and then fast (the adsorption process is as follows...). Figure 5 (As shown). This invention adjusts the electron cloud density of the amylopyrime group by adding electron-withdrawing groups to the resin. The presence of electron-withdrawing groups helps to deprotonate the amylopyrime group, reduces the pKa of the resin, increases the overall active sites of the resin, thereby improving the saturated adsorption capacity of the resin, accelerating the initial adsorption rate, and thus improving the selectivity for gallium adsorption.
[0021] Example: This embodiment uses eight different styrene resins containing electron-withdrawing groups to prepare adsorption resins with low electron cloud density amine oxime groups (referred to as Examples 1-8, where the products prepared in Examples 1, 7, and 8 are shown in the figure). Figure 6 ).
[0022] First, porous copolymer microspheres were prepared using a solvent suspension polymerization method. Under the action of a dispersant, the oil phase was dispersed in the aqueous phase to form stable beads. Free radical polymerization was initiated by temperature programming to prepare porous copolymer microspheres. Then, the resin underwent ammonium oxime modification. The nitrile groups (-CN) on the surface and inside of the microspheres underwent an electrophilic addition reaction with hydroxylamine hydrochloride, converting them into amylopectin groups (-C(NH2)=NOH), thus obtaining an adsorption resin with low electron cloud density amylopectin groups. The specific preparation method is as follows: (1) Preparation of porous copolymer microspheres A1. Reagent pretreatment: 9.8g acrylonitrile, 2.0g styrene containing electron-withdrawing groups and 5.0g divinylbenzene were passed through glass columns packed with alkaline alumina. The columns were 20cm high and 1cm in diameter. After deoxygenation by boiling in distilled water, the solution was cooled to room temperature. Polyvinyl alcohol 1788 was prepared into a 5 wt% aqueous solution and stirred at 30℃ for 30min. A2. Preparation of the oil phase system: In a 100mL beaker, add 9.8g of pretreated acrylonitrile (AN, which provides nitrile active sites for subsequent oxime modification), 2.0g of styrene containing electron-withdrawing groups (to adjust the hydrophobicity of the resin matrix, improve mechanical stability, and reduce the electron cloud density of the oxime group), and 5.0g of divinylbenzene (DVB, which constructs a three-dimensional cross-linked network to improve the mechanical strength and pore stability of the resin). Then add 8.8g of cyclohexanone and 4.4g of xylene (which, when combined with xylene, regulates the porous structure of the resin and increases the specific surface area of the resin). Stir for 5 minutes, then add 0.16g of benzoyl peroxide (BPO, which decomposes upon heating to generate free radicals and initiate monomer polymerization). Stir for 5 minutes to obtain the oil phase system. A3. Preparation of the aqueous phase system: Add 200 mL of deoxygenated distilled water (to provide a stable reaction environment) and 200 mL of 10 wt% NaCl aqueous solution (to match the oil phase density and enhance the stability of the suspension system) to a 500 mL three-necked round-bottom flask. Turn on the constant speed stirrer, adjust the speed to 150 r / min, and stir for 10 min. Add 200 mL of 5 wt% polyvinyl alcohol 1788 aqueous solution (PVA1788, to reduce the oil-water interfacial tension and inhibit bead aggregation). Place the three-necked flask in a constant temperature water bath, set the temperature to 30℃, and stir at a constant temperature for 30 min to obtain the aqueous phase system. A4. Suspension and dispersion: The oil phase system of A2 is added dropwise to the aqueous phase system of A3. During the dropwise addition, the stirring speed is maintained at 150 r / min. After the dropwise addition is completed, the stirring speed is increased to 200-250 r / min, the water bath temperature is maintained at 30℃, and the mixture is stirred at a constant temperature for 30 min to obtain a suspension. A5. Heating and Polymerization: Set the heating rate of the constant temperature water bath to 0.5℃ / min, heat to 60℃, and react at a constant temperature for 3 hours. Stir at 200 r / min, continue to heat to 80℃ at a rate of 0.5℃ / min, and react at a constant temperature for 4 hours. Then heat to 92℃ at a rate of 0.5℃ / min and react at a constant temperature for 5 hours. Then turn off the heating switch of the constant temperature water bath and let it cool naturally for 2 hours. Stop stirring, transfer the reaction liquid and beads in the three-necked flask to the Buchner funnel, turn on the vacuum pump to filter, and collect the resin beads. A6. Post-treatment: The resin beads of A5 were first washed three times with distilled water, 50 mL each time, then filtered, and then soaked and washed three times with 95% ethanol, 50 mL each time, for 10 min. The washed resin beads were then transferred to a petri dish and placed in a vacuum drying oven and dried at 60℃ and -0.09MPa for 8 h. After drying, they were taken out to obtain porous copolymer microspheres.
[0023] (2) The porous copolymer microspheres prepared in step (1) were modified by amine oxime modification: B1. Preparation of the oxime system: Add 10 mL of dichloroethane (swelling agent, to increase the pores of the porous copolymer microspheres, expose a large number of -C≡N active sites inside, and improve the oxime conversion rate) to a beaker, 20 mL of methanol, 10 mL of ethanol (to remove residual porogens, unpolymerized monomers and reagent impurities), 5 mL of water and 15 mL of triethylenetetramine solution (neutralizing agent, to release hydroxylamine), add 15.4 g of hydroxylamine hydrochloride (NH₂OH·HCl, to provide oxime precursor) and 9.0 g of sodium hydroxide (NaOH, to adjust the pH of the system to weak alkalinity and promote the oxime reaction), turn on the stirrer, and stir at 150 r / min at room temperature for 10 min; B2. Amine oxime reaction: 10g of dried PSD resin microspheres were added to a beaker and placed in a constant temperature water bath. The heating rate was set to 1℃ / min, and the temperature was raised to 70℃. The stirring speed was adjusted to 200r / min, and the reaction was carried out at a constant temperature for 8h. Then the heating switch was turned off, and the system was allowed to cool down to room temperature naturally. Stirring was stopped. The resin beads were collected by vacuum filtration using a Buchner funnel to obtain the oxime-modified resin. B3. Post-treatment of the oxime-modified resin: The oxime-modified resin of B2 was first washed with distilled water, 50 mL each time, stirring and washing for 5 min, and then filtered. The washing was repeated until the pH of the filtrate was 7.0. Then it was washed twice with 95% ethanol, 30 mL each time, soaking for 5 min. The washed oxime-modified resin was placed in a vacuum drying oven and vacuum dried at 50℃ and a vacuum degree of -0.09 MPa for 6 h. After drying, an adsorption resin with low electron cloud density oxime groups was obtained.
[0024] The structural formulas of the styrene containing electron-withdrawing groups and their corresponding adsorption resins used in Examples 1-8 are shown in Table 1.
[0025] Table 1. Structural formulas of styrene containing electron-withdrawing groups and their corresponding adsorption resins used in Examples 1-8
[0026] Comparative example: Following the synthesis method of the examples, three types of amine oxime resins were prepared: a crosslinked resin without electron-withdrawing groups (Comparative Example 1) and a crosslinked resin containing electron-donating groups -CH3 (Comparative Example 2).
[0027] The structural formulas of the styrene and its corresponding resin used in Comparative Examples 1-2 are shown in Table 2.
[0028] Table 2. Structural formulas of styrene and its corresponding resins used in Comparative Examples 1-2
[0029] Experimental example: (1) Characterization of the adsorption resins synthesized in Examples 1, 7 and 8 The successful preparation of the adsorption resins in Examples 1, 7, and 8 was verified by X-ray photoelectron spectroscopy (XPS). Characteristic elemental signals such as C, N, and O of the adsorption resins synthesized in Examples 1, 7, and 8 were clearly observed in the full XPS spectrum (see [link to XPS]). Figure 1 Simultaneously, the fine spectra of C1s, N1s, and O1s show characteristic peaks corresponding to the functional groups, confirming the successful synthesis of the resin structure under the process of this invention (see...). Figure 2-4 The C1s spectrum showed a peak at 286.5 eV (C=N), the N1s spectrum showed a peak at 399.6 eV (C=N), and the O1s spectrum showed a peak at 530.5 eV (NO). The appearance of these new peaks confirms the successful oximetization of the resin in this invention. The C1s spectrum also showed a peak at 292.0 eV (CF), confirming the successful grafting of the electron-withdrawing density group -CF3.
[0030] (2) Performance testing The adsorption capacity, adsorption equilibrium time, and gallium / vanadium adsorption ratio of the resins prepared in Examples 1-8 and Comparative Examples 1-2 were tested, and their corresponding pKa values, deprotonation rates, and gallium / vanadium adsorption ratios were calculated. The specific methods are as follows: Preparation of gallium-containing solutions: Based on the concentration of gallium ions in the circulating mother liquor of alumina produced by the Bayer process of Aluminum Corporation of China Limited, simulated Bayer solutions containing 200 mg / L Ga(III), 120 mg / L V(V), and 30 g / L Al(III) were prepared for the following experiments.
[0031] ① Adsorption capacity: Prepare 20 mL of simulated Bayer solution. Weigh 0.5 g of the resin prepared in Examples 1-8 and Comparative Examples 1-3 and add it to the simulated Bayer solution. Then place it in a water bath shaker and shake for 120 min until complete equilibrium is reached. After adsorption equilibrium is reached, remove the centrifuge tubes from the shaker one by one. Dilute the adsorbed solution to the linear range of ICP test and determine the gallium concentration C in the adsorbed solution using ICP-OES. e (Ga). The calculation formula is as follows: Gallium equilibrium adsorption capacity:
[0032] Vanadium equilibrium adsorption capacity:
[0033] Where: C0: initial concentration (mg / L); C e : Equilibrium concentration (mg / L); V: Solution volume (L); m: Mass of dry resin (g).
[0034] ② Adsorption equilibrium time: Using resin as the adsorbent, adsorption times were 10, 20, 30, 40, 50, 60, 70, 80, 90, and 120 min. The change in gallium ion concentration over time was investigated to determine the adsorption equilibrium time. The specific operation was as follows: 20 mL of simulated Bayer solution was prepared, and 0.5 g of the resin prepared in Examples 1-8 and Comparative Examples 1-3 was weighed and added to the simulated Bayer solution. The solution was then placed in a water bath shaker and shaken. The sampling points were 10, 20, 30, 40, 50, 60, 70, 80, 90, and 120 min. The centrifuge tubes were removed from the shaker sequentially according to the time points. The adsorbed solution was diluted to the linear range of ICP testing, and the gallium concentration C in the adsorbed solution was determined using ICP-OES. e (Ga).
[0035] ③Calculation method for gallium / vanadium adsorption ratio: Prepare 20 mL of simulated Bayer solution. Weigh 0.5 g of the resins prepared in Examples 1-8 and Comparative Examples 1-3 and add them to the simulated Bayer solution. Then place it in a water bath shaker and shake until complete equilibrium is reached. After adsorption equilibrium is reached, remove the centrifuge tubes from the shaker one by one. Dilute the adsorbed solution to the linear range of ICP testing. Simultaneously determine the gallium concentration C in the adsorbed solution using ICP-OES. e (Ga) and concentrated vanadium C e (V). The gallium-vanadium adsorption ratio is calculated as follows: Ga / V adsorption ratio ( ) .
[0036] ④ pKa value calculation method: Compared with the crosslinking resins of Comparative Examples 1 and 2, the electron cloud density-regulated amine oxime adsorption resin of the present invention has a lower pKa and a higher degree of deprotonation. This conclusion can be drawn using the following theoretical method: 1) Semi-neutralization titration method The ionization equation of the monoprotic weak acid HA is:
[0037]
[0038] When HA is titrated to half its volume with a monobasic base (such as sodium hydroxide), then , , ( That is, titrating HA to half. (pH of the solution at that time).
[0039] The formula for calculating buffer solutions is:
[0040] In the formula, The acid dissociation constant of the monoprotic weak acid HA is given. This represents the molar concentration of undissociated weak acid molecules HA under equilibrium conditions. In equilibrium, the conjugate base anion generated by the dissociation of a weak acid. The molar concentration of a substance.
[0041] when Sometimes, If a monoprotic weak acid is used... The solution is divided into two equal volumes, one of which is used The solution is titrated to the stoichiometric point, then mixed with another portion of the untitrated solution; the resulting mixture is the buffer system. The properties of this buffer solution are then determined. A weak acid can be obtained. of .
[0042] ⑤ Deprotonation rate calculation method: The degree of deprotonation of the amine oxime resin is calculated based on pKa.
[0043] acid dissociation constant :
[0044] In the formula, This represents the activity of hydrogen ions in the solution. The activity of the deprotonated amine oxime group, This represents the activity of the protonated amine oxime group.
[0045] Corresponding negative logarithmic form The higher the value, the more difficult it is for the oxime hydroxyl group to dissociate and for deprotonation to be achieved.
[0046] Degree of deprotonation (DoD): Under equilibrium conditions, the proportion of deprotonated active groups to total amine oxime groups, calculated as follows:
[0047] right Take the negative logarithm of both sides of the expression and combine... definition We can deduce that: ; pH-pKa form: .
[0048] The specific results are shown in Table 3. As can be seen from Table 3, compared to Comparative Examples 1 and 2, the resin of this invention has a lower pKa, a deprotonation rate of 77.62% at pH=14.5, which is 5.04 times that of Comparative Example 1 and 12.26 times that of Comparative Example 2, respectively; a gallium adsorption capacity of 6.33 mg / g, which is 84.91% and 115.31% higher than Comparative Examples 1 and 2, respectively; an adsorption equilibrium time of 79 min, which is 14.13% and 23.30% shorter than Comparative Examples 1 and 2, respectively; and a gallium / vanadium adsorption ratio of 18.54, which is 17.64% and 39.19% higher than Comparative Examples 1 and 2, respectively. Overall, it also shows significant advantages over Comparative Example 3, fully demonstrating that the resin of this invention has the characteristics of low pKa, high deprotonation rate, high adsorption capacity, fast adsorption rate, and strong adsorption selectivity.
[0049] Table 3 Performance test results of the adsorption resins prepared in Examples 1-8 and Comparative Examples 1-2
[0050] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. An adsorption resin having low electron cloud density amine oxime groups, characterized in that, The general structural formula of the adsorption resin is shown in formula (Ⅰ): (Ⅰ) Wherein, R is at least one of -NO2, -CN, -CF3, -CCl3, -SO3H and halogen.
2. The adsorption resin with low electron cloud density amine oxime groups according to claim 1, characterized in that, The halogen is at least one of F, Cl, Br and I.
3. The method for preparing the adsorption resin with low electron cloud density amine oxime groups as described in claim 1 or 2, characterized in that, Includes the following steps: (1) Preparation of porous copolymer microspheres: A1. Oil phase preparation: Mix the functional monomer, styrene containing electron-withdrawing groups, crosslinking agent and porogen, then add the initiator and mix well to obtain the oil phase system. A2. Preparation of aqueous phase: Mix the aqueous dispersant and density regulator evenly, then add the dispersion stabilizer, and stir at 20-30℃ for 20-30 min to obtain the aqueous phase system; A3. Suspension and dispersion: Under stirring conditions and at 20℃-30℃, the oil phase system of A1 is added dropwise to the aqueous phase system of A2, and then the mixture is stirred at a constant temperature of 200-250r / min for 15-30min to obtain a suspension. A4. Heating polymerization: Under stirring conditions, the suspension of A3 is reacted at 60-70℃ for 1-3 hours; then the temperature is raised to 70-80℃ and the reaction is kept at a constant temperature for 2-4 hours; then the temperature is raised to 85-98℃ and the reaction is kept at a constant temperature for 3-5 hours. The resulting product is cooled to room temperature, filtered, and the resin beads are collected. A5. Post-treatment: The resin beads of A4 are washed sequentially with distilled water and 95%-99.9% ethanol, and then the resin beads are dried to obtain porous copolymer microspheres. (2) The porous copolymer microspheres prepared in step (1) were modified by amine oxime modification: B1. Preparation of the oxime system: Dichloroethane, methanol, ethanol, water, triethylenetetramine solution, modifier and pH adjuster are mixed to prepare the oxime system; B2, Amine oxime reaction: The porous copolymer microspheres obtained in step (1) are added to the oxime system of B1 and reacted at 70-80℃ for 6-10 hours under stirring conditions. The resulting product is then filtered and the resin beads are collected to obtain the oxime resin. B3. Post-treatment of the amine oximated resin: The amine oximated resin of B2 is first washed with distilled water until the pH of the filtrate is 6.8-7.2, then washed with 95%-99.9% ethanol, and then dried to obtain the final product.
4. The preparation method according to claim 3, characterized in that, The functional monomer is acrylonitrile; the crosslinking agent is divinylbenzene; the porogen is at least one of cyclohexanone, isooctane, n-heptane, liquid paraffin, toluene, and xylene; and the initiator is benzoyl peroxide or azobisisobutyronitrile.
5. The preparation method according to claim 3, characterized in that, The styrene containing the electron-withdrawing group is one of the following compounds: Wherein, R is at least one of -NO2, -CN, -CF3, -CCl3, -SO3H and halogen.
6. The preparation method according to claim 3, characterized in that, The aqueous dispersant is deoxygenated distilled water; the density regulator is an aqueous NaCl solution; and the dispersion stabilizer is at least one of PVA1788, gelatin, carboxymethyl cellulose, and sodium lignosulfonate.
7. The preparation method according to claim 3, characterized in that, The modifier is hydroxylamine hydrochloride; the pH adjuster is NaOH.
8. The application of the adsorption resin with low electron cloud density amine oxime groups as described in claim 1 or 2 in the extraction of gallium from bauxite.
9. A method for extracting gallium from bauxite, characterized in that, Gallium in bauxite can be extracted by resin adsorption using the adsorption resin with low electron cloud density amine oxime groups as described in claim 1 or 2.
